PENGARUH ASPEK PRILAKU TERHADAP PENDAPATAN PETERNAK SAPI ACEH (BOS-BIBOS) DI KECAMATAN LANGSA TIMUR KOTA LANGSA - M.Khairul Fadli; Cut Gustiana; Faoeza Hafiz Saragih; Kiagus M. Zain Basriwijaya (Jurnal Inovasi Penelitian, 2022)
This study aims to analyze the effect of behavioral aspects on the income of Aceh cattle breeders (Bos-Bibos) in East Langsa District, Langsa City. This research was conducted in East Langsa District, Langsa City. The sampling technique used disproportionate stratified random sampling technique with a total sample of 41 people. To determine the effect of behavioral aspects on the income of Aceh cattle breeders (Bos-Bibos) in East Langsa District, Langsa City, statistical analysis using multiple linear regression method was used. Data processing was performed using SPSS computer software. The results of this study indicate that the skill variable has a significant effect on the income of Aceh cattle breeders (Bos-Bibos) in East Langsa District, Langsa City. and the variable farmer knowledge and attitude does not have a significant effect on the income of Aceh cattle breeders (Bos-Bibos) in East Langsa District, Langsa City.